Uso do Wordwall como recurso pedagógico na aprendizagem de vocabulário de Língua Inglesa no 2° ano do Ensino Fundamental - Diniz, Karla Virgínia de Sousa (2025)
This research investigated the use of the Wordwall platform as a pedagogical resource for teaching English vocabulary to second-grade students in a public school in João Pessoa, Brazil. Guided by the premise that this Virtual Learning Tool (VLT) can significantly enhance the teaching-learning process, the study investigated the use of the Wordwall as a didactic resource in English language teaching, verifying its contribution to the expansion of vocabulary. The study adopted an action research methodology, with interventions in three second-grade classes, comparing traditional lessons (Type A) with lessons using Wordwall (Type B). These lessons incorporated thematic vocabulary sequences using various activity formats available on the platform, such as memory games, matching exercises, interactive quizzes, and gamified activities. The results indicated that the use of Wordwall promoted greater student engagement, increased motivation, and improved performance, evidenced by both higher accuracy rates and reduced response times in activities. The pre- and post-test activities were highly valuable tools in measuring student performance. Wordwall proved to be a promising tool for teaching English vocabulary in early elementary education, aligning with the digital literacy competencies outlined in the Brazilian National Common Curriculum guidelines (BNCC). The study emphasized the need for teacher training programs to help teachers use the Wordwall and suggested the development of an instructional prototype for teacher professional development. This research contributes to the discussion on Digital Information and Communication Technologies (DICT) in basic education, providing concrete evidence of the benefits of gamification in the learning process.